Role of Exosomes in Brain Diseases - Zhang, Nan; He, Fengling; Li, Ting; Chen, Jinzhi; Jiang, Liping; Ouyang, Xin-Ping; Zuo, Lielian (Frontiers in Cellular Neuroscience, 2021)
Exosomes are a subset of extracellular vesiclesthat are capable of accomplishing communication between cells as messengers.Non-coding RNAs, proteins, lipids, and microRNAs are delivered by the exosomes to target molecules (such as proteins, mRNAs or DNA) of host cells, thereby playing a key role in the maintenance of normal brain function. However, exosomes are also involved in the occurrence, prognosis, and clinical treatment of brain diseases, such as Alzheimer's disease, Parkinson's disease, stroke, and traumatic brain injury. In this review, we have summarized the new findings that elucidate the role of exosomes in the occurrence, prognosis, and treatment of brain diseases.